Penerapan Labeling Qr Code untuk Memonitor Peralatan Kerja PT XYZ Menggunakan Diagram Activity - Putri, Andani Rizki; Widodo, Condro (VISA: Journal of Vision and Ideas, 2024)
In this era of globalization, technical progress has a huge influence on companies, especially on the efficiency of operational activities in companies. One technology that stands out is the QR Code used by PT XYZ to monitor their work equipment. QR Codes have the benefit of allowing you to store and access equipment information instantly using electronic devices such as smartphones, tablets and other electronic devices. The use of this QR Code has increased the efficiency of company asset management, accelerated the monitoring process, and reduced the possibility of errors associated with the previous manual approach. QR Codes also enable improved maintenance planning, lower emergency maintenance costs, and increase equipment safety and security. To better understand the use of QR Codes in controlling work equipment at PT XYZ, this research uses a qualitative approach such as interviews, observation and documentation, as well as visualizing it with activity diagrams. In conclusion, QR Codes have proven to be an effective and efficient option for improving asset management and staff performance in businesses.